Novel continuous spectrum generation system using a nano-waveguide for white light, short and sub-millimeter waves use - Mitatha, S.; Yupapin, P. P. (My University, 2009)
We propose a novel system of a nano-waveguide that can be used to generate the continuous spectrum, that is, white light. The simultaneous generation of short and sub-millimeter waves can also be generated by using either dark or bright soliton schemes. A system consists of two microring and a nanoring resonators that can be integrated into a single system. The large bandwidth is generated by a soliton pulse within a Kerr type nonlinear medium where the continuous bandwidth or wavelength can be performed. Results of the bright soliton obtained have shown the potential of using the technique for white light source generation and detection, which is discussed. The simultaneous generation of short and millimeter waves using dark soliton is also proposed. The advantage is that the large bandwidth separation of the short and sub-millimeter waves can be obtained, which is allowed the simultaneous generation of short and millimeter waves. © 2009 Wiley Periodicals, Inc.
Keywords: Continuous spectrum; Nano-waveguide; Short wave; Sub-millimeter wave; White light